Saving a Child’s Elbow Joint: A Novel Reconstruction for a Tumour of the Distal Humerus - Calogero Graci; Czar Louie Gaston; Robert Grimer; Lee Jeys; Korhan Ozkan (Case Reports in Orthopedics)
Reconstruction after wide resection of a malignant bone tumor can be obtained using several techniques such as the use of prostheses, allograft, autograft, or combined procedure. We describe a 12-year-old girl with parosteal osteosarcoma of the distal right humerus treated by en bloc resection, intraoperative extracorporeal irradiation, and implantation. We inserted a nonvascularised fibular autograft through the middle of irradiated graft to obtain a greater stability. We have not recorded any complication associated with this technique such as nonunion, pathological fracture, infection, and bone necrosis and we obtained an excellent functional result. 10 years after surgery, the patient had no recurrence. Extracorporeal irradiation and reimplantation is a valid and inexpensive technique for the treatment of bone tumors when there is reasonable residual bone stock. With this procedure we have a precise fit being the patient’s own bone. In this way we avoid all the problems related to the adaptation of the shape and size.